2022
DOI: 10.1021/acschembio.2c00422
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolite Produced by Gut Microbes Represses Phage Infections in Vibrio cholerae

Abstract: Vibrio cholerae is the causative agent of the severe diarrheal disease cholera. Bacteriophages that prey on V. cholerae may be employed as phage therapy against cholera. However, the influence of the chemical environment on the infectivity of vibriophages has been unexplored. Here, we discovered that a common metabolite produced by gut microbeslinear enterobactin (LinEnt), represses vibriophage proliferation. We found that the antiphage effect by LinEnt is due to iron sequestration and that multiple forms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…It has been reported that iron starvation actually has the opposite effect in Vibrio cholerae : it reduces burst size and delays phage-mediated cell lysis. 27 In line with the V. cholerae study, we observed that when B. subtilis grew next to Streptomyces sp. I8-5, the plaque development of SPO1 was slower than plaque development alone, suggesting that iron sequestration does not accelerate phage replication (Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…It has been reported that iron starvation actually has the opposite effect in Vibrio cholerae : it reduces burst size and delays phage-mediated cell lysis. 27 In line with the V. cholerae study, we observed that when B. subtilis grew next to Streptomyces sp. I8-5, the plaque development of SPO1 was slower than plaque development alone, suggesting that iron sequestration does not accelerate phage replication (Fig.…”
Section: Resultssupporting
confidence: 80%
“…In fact, the plaques were substantially smaller under EDDHA treatment, possibly due to the aforementioned slowing of phage proliferation under iron limitation. 27 Therefore, our results demonstrate that iron sequestration extends phage infection on B. subtilis by inhibiting its sporulation into dormant, phage-tolerant cells.…”
Section: Resultsmentioning
confidence: 58%